The Evolution of Portraiture in Contemporary Visual Arts - Prayoga Saputra; Ethan Tan; Ava Lee (Journal of Humanities Research Sustainability, 2024)
Background. This research aims to explore the evolution of portrait art in contemporary visual art, focusing on how portrait evolved from physical representation to a medium of social communication rich in critical messages and social themes. Purpose. The background of this research is based on the increasing use of digital media and the changing audience preference for portraits that convey relevant issues such as identity and social inequality.    Method. This research uses a qualitative method with a descriptive-analytical approach, through in-depth interviews with artists and participatory observation in art galleries. Results. The results show that contemporary portraits are more than just visual works; It becomes an effective advocacy tool, blending aesthetics with complex social issues. Portraits now not only display appearances, but also convey a powerful narrative that invites the audience to engage in the process of interpretation and reflection. Conclusion. The conclusion of the study underscores that contemporary portrait art plays an important role in strengthening social awareness and offers a new perspective on visual art as a medium capable of driving social change.